A spectroscopic study of the electronic effects on copper (II) and copper (I) complexes of ligands derived from various substituted benzyaldehyde- and cinnamaldehyde- based schiff bases - Magwa, Nomampondo Penelope (Rhodes University, Faculty of Science, Department of Chemistry, 2010)
Several Schiff base ligands, N, N"Ÿ-(aryl)benzyaldiimine ligands (R-BEN); N, N"Ÿ-(aryl)benzyaldiamine dihydrochloride ligands (R-BENH"¢2HCl); N, N"Ÿ-(aryl)benzyaldiamine ligands (R-BENH); N, N"Ÿ-bis(cinnamaldiimine) ligands (R-CA2EN) were synthesized for the investigation of the electronic effect of the substituents at para-position of the Schiff base ligands and their copper complexes. The synthesis of Schiff bases was carried out by reacting a series of para-substituted benzyaldehyde, and para-substituted cinnamaldehyde with ethylenediamine. The imine group of Schiff bases, N, N"Ÿ-(aryl)benzyaldiimine ligands and N, N"Ÿ-bis(cinnamaldiimine)ligands were reduced to corresponding amines with sodium borohydride in methanol These ligands, N, N"Ÿ-(aryl)benzyaldiamine ligands (H-BENH), N, N"Ÿ-bis(cinnamaldiimine)ligands (CA2EN) were reacted with copper(II) dihalide and copper(I) monohalide ions respectively to form complexes. The ligands and their complexes were analysed using elemental analyses, FT-IR spectroscopy (mid-IR), UV/vis in aprotic and protic solvents,while mass spectrometry, 1H-NMR and 13C-NMR were used to further analyse the ligands. By using substituent parameters, both the single and dual substituent parameters with the spectroscopic data obtained from the spectroscopic techiques mentioned above, it was hoped to monitor and determine whether the electronic effects (resonance or inductive effcets) was predominantly within the Schiff base ligands and copper complexes. The NMR studies with dual substituent parameters suggest that the effects of the substituents are transimitted through the ligands, via resonance effects and that the phenyl group is nonplanar with the azomethine in N, N"Ÿ-(aryl)benzyaldiimine ligands. The presence of an extra double bond in Schiff base {(N, N"Ÿ-bis(cinnamaldiimine) ligand)} altered the electron density. The UV/vis studies showed that the symmetry of the N, N"Ÿ-bis(4-R-benzyl)-1, 2-diaminoethanedihalidecopper(II) complexes were predominantly tetrahedral for both chloro and bromo complexes. The correlation studies from mid-infrared were beneficial in monitoring the effect experienced by N, N"Ÿ-(aryl)benzaldiimine ligands, the studies suggest that the inductive effect is more pronounced at the C=N.
Keywords: Copper -- Analysis; Schiff bases; Organometallic compounds